Role of digitalization in environment, social and governance, and sustainability: Review-based study for implications - Xu, Jiaqi; She, Shengxiang; Liu, Wen (Frontiers in Psychology, 2022)
Digitalization gives people access to a vast network of untapped data, which has the potential to help society and the environment. Smart systems connected to the internet can systematically provide a unique opportunity to solve difficulties related to long-term sustainability. The goals are to create an egalitarian, ecologically sustainable, and healthy society. Technological resources are envisioned as game-changing instruments. Three key concerns integration benefits are highlighted here: (i) sustainable development goals, (ii) socio-economic development, and (iii) the role of digital technology in environmental sustainability. This viewpoint describes the potential that digitization can create a future sustainable society. The technological network would unite the urban and rural worlds under a shared banner of sustainable development, keeping all social elements in the loop. Nations that take a comprehensive strategy will be able to provide equitable growth and an efficient, sustainable, and digital existence for their citizens. As a result, digitization provides better living conditions, active public involvement, clean governance, and transparency in public welfare programs and processes. People who are well-informed, self-aware, and digitally equipped will be better learners, thinkers, reformers, participators, and change and growth agents, marching forward on sustainable progress. The advantages of digitization in hastening the transition to sustainable industrial processes and improving people's health and happiness are explored. Finally, the perspective encapsulates the advantages of digitization by offering a holistic vision of how technology could aid in addressing major challenges such as endangered world biodiversity and climate change.